KERJASAMA INDONESIA-THAILAND DALAM PEMBERANTASAN NARKOBA MENUJU DRUG-FREE ASEAN 2015 - Wiwiek Rukmi Dwi Astuti; Sarah Tabitha; Nurmasari Situmeang (Andalas Institute of International Studies, 2022)
The drug problem which is a problem from year to year is increasingly complex and makes the drug problem a transnational problem which to eradicate it requires cooperation from various international and national layers. ASEAN as a Southeast Asian organization realizes one of the organization's ideals, namely a Southeast Asian region that is free from drugs through the Drug Free ASEAN 2015’s declaration is committed to strengthening cooperation in overcoming drug abuse with a jointly designed work plan. In its implementation, Indonesia and Thailand hold cooperation with the hope of eradicating drugs in both countries, because as we know that the drug problem cannot be carried out alone. In cooperation, Indonesia and Thailand carried out several activities that were considered effective enough to help overcome this crucial problem. The method of this research is a qualitative using the theory of Regionalism and International Cooperation in its analysis which results in the conclusion that the Cooperation between Indonesia and Thailand is apart from the current massive condition of the drug problem, Cooperation between Indonesia and Thailand is running effectively with the attitude of the two countries being cooperative and various ongoing activities. in accordance with the ideals of both countries.